Nasionalisme di Era Internet - Danu Widhyatmoko (Humaniora, 2015)
Nationalism and nationality of a country life are moving into the new phase. Internet has become a new medium that opens up so many opportunities to create a sense of nationalism for the country. This paper contains a review of nationalism in the age of the Internet. This paper begins with understanding nationalism, the character of the Internet, social media and nationalism in the era of the Internet. Research method used in this paper is literature study, continued with reflective data analysis. With reflective analysis method, the authors analyzed data from the data collection has been carried out for comparison between the existing literature by circumstances or phenomena that occur, so that the conclusions of rational and scientific data can be obtained.